AB0393 Efficacy and Safety of Etanercept (ETN) in Patients with Moderately Active Rheumatoid Arthritis (RA) despite Disease-Modifying Antirheumatic Drug (DMARD) Therapy. (10th June 2014) - Hobbs, K.; Chung, J.; Bitman, B.; Wang, B.; Nussbaum, J.; Collier, D.H.
Abstract : Background: Patients (pts) with moderately active RA represent a medically important subset of RA pts. Numerous clinical trials indicate that a substantial number of pts with moderate RA can achieve recommended treatment targets. Objectives: To evaluate whether adding ETN to standard-of-care DMARD therapy in pts with moderate RA is superior in inducing LDA (Disease Activity Score using 28 joints with C-reactive protein [DAS28-CRP] <3.2) compared with continued DMARD therapy. Methods: This randomized, double-blind, placebo (PBO)-controlled study enrolled pts with DAS28-CRP >3.2 and ≤5.1 despite being on stable DMARD therapy at screening. After a screening window of up to 31 days, pts were randomized to receive ETN 50mg or PBO weekly for 12 weeks followed by ETN 50mg weekly for an additional 12 weeks. Endpoints included rates of LDA at week 12 (primary endpoint), remission (DAS28-CRP <2.6), American College of Rheumatology (ACR) responses, change in Health Assessment Questionnaire Disability Index (HAQ-DI), and safety. Missing data were imputed using the last observation carried forward. Results: For the primary analysis set of 210 enrolled pts (104 PBO; 106 ETN), baseline mean (standard deviation [SD]) DAS28-CRP was 4.88 (0.81) and 4.88 (0.69) for PBO and ETN pts, respectively, and mean (SD) HAQ scores were 1.20 (0.68) and 1.28 (0.64). At week 12, more pts randomized to ETN than PBO were in DAS28-CRP LDA (33% vs 21%; P =0.055) and DAS28-CRP remission (19% vs 12%; P =0.14) but the results were not statistically significant. Improvement in the PBO treatment group and lack of continued improvement in the ETN treatment group was observed between weeks 8 and 12 as rates of DAS28-CRP LDA were statistically significantly different at week 8 (ETN 34%, PBO 16%; P =0.003). Of note, of the 210 pts in the primary analysis set, 194 (92%) pts had moderate RA at screening but only 122 (58%) pts had moderate RA at baseline. For the subset of pts with moderate disease at baseline, 18% of PBO pts and 42% of ETN pts achieved LDA at week 12. Rates of ACR20, ACR50, and ACR70 responses improved from week 2 through week 24 in both treatment groups. At week 12, ACR20, ACR50, and ACR70 responses were observed in 30%, 13%, and 1% of PBO pts, respectively, and 42%, 22%, and 6% of ETN pts. Mean change (SD) in HAQ-DI score was -0.20 (0.43) for PBO pts and -0.39 (0.54) for ETN pts at week 12 ( P =0.024). No new or unexpected safety findings were observed. Conclusions: ETN led to the induction of LDA in a greater proportion of pts compared with PBO in pts with moderate disease, although the difference was not statistically significant at week 12 in the primary analysis set of pts with moderate disease at screening. A post hoc analysis of the 122/210 pts who maintained moderate disease at baseline showed consistent evidence of efficacy across a broad set of outcome measures. Acknowledgements: Study funded by Immunex, a wholly owned subsidiary of Amgen Inc. and by Wyeth, which was acquired by Pfizer in October 2009. Julie Wang (Amgen Inc.) and Julia R. Gage (on behalf of Amgen Inc.) provided medical writing support. Disclosure of Interest: K. Hobbs Consultant for: Amgen Inc., J. Chung Shareholder of: Amgen Inc., Employee of: Amgen Inc., B. Bitman Shareholder of: Amgen Inc., Employee of: Amgen Inc., B. Wang Shareholder of: Amgen Inc., Employee of: Amgen Inc., J. Nussbaum Shareholder of: Amgen Inc., Employee of: Amgen Inc., D. Collier Shareholder of: Amgen Inc., Employee of: Amgen Inc. DOI: 10.1136/annrheumdis-2014-eular.1253